Gastro-esophageal varices - Zumaeta Villena, Eduardo (2007)
Portal hypertension in the cirrhotic patient is associated not only to physiologic, humoral and hemodynamic changes, but also with mechanical phenomena associated to the rigid and nodular liver architecture. The formation of collateral circulation particularly in the submucosa of the distal esophagus, known as esophageal varices is a common complication, and its importance relies on the very high mortality associated with its rupture. The degree of variceal prominence and the probability of rupture correlates with the clinical stage of cirrhosis. Currently we count with efﬁcacious drugs in the scenario of an acute variceal hemorrhage, along with endoscopic hemostatic techniques like sclerotherapy and variceal ligation or radiologically placed portosystemic shunts (TIPS) as a rescue modality. On the other hand, the probability of preventing the ﬁrst bleeding or the rebleeding in the patient who already had a ﬁrst hemorrhage (primary and secondary prophylaxis respectively) are of extreme interest for the physician caring for a cirrhotic patient. This article extensively reviews those important issues.